Quantization in magnetoresistance of strained InSb whiskers - Druzhinin, A.; Ostrovskii, I.; Khoverko, Y.; Liakh-Kaguy, N. (Физика низких температур, 2019)
Strain influence on the longitudinal magnetoresistance for the n-type conductivity InSb whiskers doped by Sn
to concentration 6·10¹⁶–6·10¹⁷ сm⁻³ was studied in the temperature range 4.2–40 K and magnetic field up to 10 T.
The Shubnikov–de Haas oscillations at low temperatures were observed in the strained and unstrained samples in
all range of doping concentrations and magnetic fields. The character of longitudinal magnetoresistance dependences was analyzed and compared with theoretical one. The whisker magnetoresistance alters its sign with increasing magnetic field. It is positive at weak magnetic fields and becomes negative at higher magnetic fields.
Possible mechanism of the large value of negative magnetoresistance (NMR) was discussed in the InSb whiskers
with doping concentration in the vicinity to metal–insulator transition. The origin of large NMR was explained
by the existence of classical size effect and boundary scattering during conductance in subsurface whisker layers. На основі досліджень поздовжнього магнітоопору ниткоподібних кристалів InSb n-типу провідності, легованих Sn до
концентрацій 6·10¹⁶–6·10¹⁷ см⁻³
, в інтервалі температур 4,2–
40 К і магнітних полів до 10 Тл виявлено осциляції Шубнікова–де Гааза в деформованих і недеформованих зразках. Проведено аналіз поведінки польових залежностей магнітоопору
згідно відомих теоретичних уявлень. Встановлено, що з підвищенням індукції магнітного поля магнітоопір ниткоподібних кристалів InSb змінює свій знак від позитивного до
від’ємного. Обговорюються механізми, які зумовлюють появу високих значень від’ємного магнітоопору (ВМО) у зразках InSb з концентрацією легуючої домішки, що відповідає
близькості до переходу метал–діелектрик. Існування ВМО
пов’язане з класичним розмірним ефектом, а також гранічним розсіюванням у провідності приповерхневих шарів мікрокристалів. На основе исследований продольного магнитосопротивления нитевидных кристаллов InSb n-типа проводимости,
легированных Sn до концентраций 6·10¹⁶–6·10¹⁷ см⁻³
, в интервале температур 4,2–40 К и магнитных полей до 10 Тл
обнаружены осцилляции Шубникова–де Гааза в деформированных и недеформированных образцах. Проведен анализ
поведения полевых зависимостей магнитосопротивления согласно известным теоретическим представлениям. Установлено, что с повышением индукции магнитного поля магнитосопротивление нитевидных кристаллов InSb меняет свой знак от
положительного к отрицательному. Обсуждаются механизмы,
которые обусловливают появление высоких значений отрицательного магнитосопротивления (ОМС) в образцах InSb с
концентрацией легирующей примеси, соответствующей близости к переходу металл–диэлектрик. Существование ОМС
обусловлено классическим размерным эффектом, а также
граничным рассеиванием в проводимости приповерхностных
слоев микрокристаллов.